Engineering-based Kindergarten Mathematics Learning Plan (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2020)
Exposing young learners to early engineering concepts allows them to practice important skills, discover capabilities, and set a foundation for successful learning in their schooling. The future success of children lies in the ability to master basic computational skills, which are prerequisites in doing more advanced and more complex mathematical problems. This study was conducted to determine the level of competence of mathematics skills of Kindergarten pupils of Ilocanos Elementary School as a basis in the formulation of an Engineering-Based Kindergarten Learning Plan. The study employed quasi-experimental research utilizing a validated teacher-made-test. The respondents of the study were the Kindergarten pupils, morning and afternoon sessions of Ilocanos Elementary School, City of San Fernando, La Union during the School Year 2019-2020. The result showed that the level of competence of mathematics skills of Kindergarten pupils before the pre-test was moving toward mastery, which meant that the learners are on their way to achieving the mastery level. On the other hand, the post-test result illustrated that improved from moving towards mastery to closely approximating mastery after the intervention lesson was conducted; thus, their level of competence varies significantly from pre-test to post-test. It is concluded that the Engineering-Based Kindergarten Mathematics Learning Plan enhanced their competencies in Mathematics; hence, the developmentally appropriate material validated by experts is recommended for use to pre-school teachers.
Keywords: engineering-based teaching approach, kindergarten mathematics, learning plan